Boost student completion as a student‐centered institution. Issue 2 (25th September 2017) - Sutton, Halley
Abstract : "I like to say that I have the heart of an advisor and the brain of an academic, " said Lynn Mahoney, Ph.D., provost and vice president for academic affairs at California State University, Los Angeles. That mentality, born out of Mahoney's background as both a lecturer and academic advisor, has been at the forefront of Mahoney's work to improve time‐to‐degree and completion rates on campus. "[Throughout my career] I've been consumed with the inadvertent obstacles we place in students' way as they attempt to achieve their degrees, " Mahoney said. She shared strategies and changes the Cal State LA campus is making to improve completion rates.